Antipathy towards Literary Translation and the Problematics of Change Reception - Aldalain, Mohammad N. (International Journal of Psychosocial Rehabilitation, 2020)
Translation is approached from various theoretical frameworks and perceived as a field of knowledge dispersed across several disciplines. While it seems that the importance of literary translation in cultural communication and transplanting literary values is widely recognised, possibilities for the translated literary text to stand for the original is still under debate, sometimes turning to further provocative situations questioning if literary translation is possible at all. This starts with the original literary piece observed as inimitable and its content must be kept inviolate. This paper argues that antipathy towards literary translation and translated works start with hostility towards change; a metathesiophobic attitude still within linguistic and cultural ethnocentricities. The paper points out that translation is about making change to the original, it does not exist without upsetting its constructs, and that the sources of such antipathetic attitudes are our tolerance to change as well as our understanding of our own language and culture. The paper makes reference to the translation of Joseph Conrad’s Falk as it stands as an example of multilayered change.